NUCLEOCYTOPLASMIC shuttling of ETHYLENE RESPONSE FACTOR 5 mediated by nitric oxide suppresses ethylene biosynthesis in apple fruit. Issue 5 (23rd March 2022) - Ji, Yinglin; Xu, Mingyang; Liu, Zhi; Yuan, Hui; Lv, Tianxing; Li, Hongjian; Xu, Yaxiu; Si, Yajing; Wang, Aide
Summary: Nitric oxide (NO) is known to modulate the action of several phytohormones. This includes the gaseous hormone ethylene, but the molecular mechanisms underlying the effect of NO on ethylene biosynthesis are unclear. Here, we observed a decrease in endogenous NO abundance during apple ( Malus domestica ) fruit development and exogenous treatment of apple fruit with a NO donor suppressed ethylene production, suggesting that NO is a ripening suppressor. Expression of the transcription factor MdERF5 was activated by NO donor treatment. NO induced the nucleocytoplasmic shuttling of MdERF5 by modulating its interaction with the protein phosphatase, MdPP2C57. MdPP2C57‐induced dephosphorylation of MdERF5 at Ser260 is sufficient to promote nuclear export of MdERF5. As a consequence of this export, MdERF5 proteins in the cytoplasm interacted with and suppressed the activity of MdACO1, an enzyme that converts 1‐aminocyclopropane‐1‐carboxylic acid (ACC) to ethylene. The NO‐activated MdERF5 was observed to increase in abundance in the nucleus and bind to the promoter of the ACC synthase gene MdACS1 and directly suppress its transcription. Together, these results suggest that NO‐activated nucleocytoplasmic MdERF5 suppresses the action of ethylene biosynthetic genes, thereby suppressing ethylene biosynthesis and limiting fruit ripening.